Randomised controlled trials or structural models (or both... or neither ...)? - Fafchamps, M (Oxford University Press, 2011)

(untitled)
The March 2011 Annual Conference of the Centre for the Study of African Economies marked the 25th anniversary of the Centre. As part of the conference, a methodology update was presented in the form of a plenary panel session devoted to randomised controlled trials (RCTs) and their relationship—or lack thereof—with structural models. The three papers presented at the plenary session are reproduced here, following this short introduction. They complement each other well to give an up-to-date assessment of the role of RCTs in the practice of development economics.